2021
DOI: 10.3390/ijms222312736
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Huntington’s Disease

Abstract: Methylation of cytosine in CpG dinucleotides is the major DNA modification in mammalian cells that is a key component of stable epigenetic marks. This modification, which on the one hand is reversible, while on the other hand, can be maintained through successive rounds of replication plays roles in gene regulation, genome maintenance, transgenerational epigenetic inheritance, and imprinting. Disturbed DNA methylation contributes to a wide array of human diseases from single-gene disorders to sporadic metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Research surrounding neurodegenerative ailments such as Alzheimer's Disease has demonstrated generalized hypermethylation of brain tissues, coupled with an elevated presence of 5‐hydroxymethylcytosine (5hmC) in the afflicted cells (Coppieters et al, 2014). Despite that, in Parkinson's and Huntington's diseases both hyper and hypo‐methylation of DNA can be observed (it depends on the gene promotor site) (Wüllner et al, 2016; Zsindely et al, 2021). Cancer is also another example of an age‐related disease that is affected by altered DNA methylation patterns.…”
Section: Epigenetic Changes In Agingmentioning
confidence: 99%
“…Research surrounding neurodegenerative ailments such as Alzheimer's Disease has demonstrated generalized hypermethylation of brain tissues, coupled with an elevated presence of 5‐hydroxymethylcytosine (5hmC) in the afflicted cells (Coppieters et al, 2014). Despite that, in Parkinson's and Huntington's diseases both hyper and hypo‐methylation of DNA can be observed (it depends on the gene promotor site) (Wüllner et al, 2016; Zsindely et al, 2021). Cancer is also another example of an age‐related disease that is affected by altered DNA methylation patterns.…”
Section: Epigenetic Changes In Agingmentioning
confidence: 99%
“…During the 5 mC to cytosine conversion, intermediate products are generated, such as 5caC, 5 fC, and 5hmC. However, recent studies have found that certain products exist stably and modulate diseases [ 115 ]. However, due to the paucity of literature on intermediates, the focus of this study will be on 5 mC in diabetic wound repair.…”
Section: Epigenetic Modification In Diabetic Wound Healingmentioning
confidence: 99%
“…Abnormalities of 5mC have been widely reported in neurodegenerative diseases, such as Parkinson’s disease (PD) and Huntington’s disease (HD) [ 18 , 19 , 20 ]. Psychiatric disorders are characterized by impairment in cognition, emotion regulation, or behavior, and typically include bipolar disorder (BD) and schizophrenia.…”
Section: Altered 5mc Pattern In Schizophreniamentioning
confidence: 99%